Моделирование регулируемых асинхронных электроприводов с согласующими редукторами и трансформаторами - Петрушин, В.С.; Якимец, А.М.; Еноктаев, Р.Н. (Електротехніка і електромеханіка, 2015)
Исследована работа разных асинхронных двигателей в составе регулируемых электроприводов, которые выполняют
одну и ту же техническую задачу, с учетом включения таких элементов, как согласующие трансформатор и редуктор. Проведено сопоставление характеристик двигателей в статических и динамических режимах. Определены
энергетические, массогабаритностоимостные показатели электроприводов. Обоснована возможность выбора лучшего варианта привода, как по вышеуказанным показателям, так и по стоимости потерь активной энергии. Досліджено роботу різних асинхронних двигунів у складі регульованих електроприводів, що виконують одну і ту ж
технічну задачу, з урахуванням включення таких елементів, як узгоджувальні трансформатор і редуктор. Зроблено
зіставлення характеристик двигунів в статичних та динамічних режимах. Визначено енергетичні, масогабаритновартісні показники електроприводів. Обґрунтовано можливість вибору кращого варіанту приводу, як за вищевказаними показниками, так і за вартістю втрат активної енергії. Purpose. Working out of mathematical models of the speedcontrolled induction electric drives ensuring joint consideration
of transformers, motors and loadings, and also matching reducers and transformers, both in static, and in dynamic regimes for
the analysis of their operating characteristics. Methodology. At
mathematical modelling are considered functional, mass, dimensional and cost indexes of reducers and transformers that
allows observing engineering and economic aspects of speedcontrolled induction electric drives. The mathematical models
used for examination of the transitive electromagnetic and electromechanical processes, are grounded on systems of nonlinear
differential equations with nonlinear coefficients (parameters of
equivalent circuits of motors), varying in each operating point,
including owing to appearances of saturation of magnetic system and current displacement in a winding of a rotor of an induction motor. For the purpose of raise of level of adequacy of
models a magnetic circuit iron, additional and mechanical
losses are considered. Results. Modelling of the several speedcontrolled induction electric drives, different by components, but
working on a loading equal on character, magnitude and a demanded control range is executed. At use of characteristic families including mechanical, at various parameters of regulating
on which performances of the load mechanism are superimposed, the adjusting characteristics representing dependences of
a modification of electrical, energy and thermal magnitudes
from an angular speed of motors are gained. Originality. The
offered complex models of speed-controlled induction electric
drives with matching reducers and transformers, give the
chance to realize well-founded sampling of components of
drives. They also can be used as the design models by working
out of speed-controlled induction motors. Practical value. Operating characteristics of various speed-controlled induction
electric drives are observed and depending on the chosen measure including measure of cost of losses of active energy, sampling of the best alternative of the drive is realized.